A PR CRISIS MANAGEMENT APPROACH OF INTERPERSONAL VIOLENCE IN AS PORTRAYED IN MALAYSIAN INDEPENDENT ONLINE MEDIA - Zanuddin, Hasmah; Saifuddin, Norizzati (International Journal of Psychosocial Rehabilitation, 2020)
Interpersonal violence is a violence that has increasingly occurred in our society and often reported in the news. This interpersonal violence has become a concern in our society which needs to be addressed to the community. Five components of interpersonal violence is comprising of youth violence, child maltreatment, intimate violence, elder abuse and sexual violence. PR crisis management is an extremely tense fight to confront the situation. Online news has altered the practice of PR crisis management and change the views of people. The purpose of conducting a study on this issue is to determine the PR crisis management of Malaysian independent online news in interpersonal violence cases. The objectives of this study are to study the crisis response, information giving strategies, and reputational repair strategies used in interpersonal violence reporting in Malaysian independent online news. This study used quantitative content analysis by analysing 140 news articles from two selected independent online news as the sample of this study. Two independent online news used in this study which includes Malaysiakini.com and Freemalaysiamtoday.com. From this study, PR crisis management was being used to reduce the problem and presented how interpersonal violence issue should be handling. This result can be used to plan future crisis management strategies in the same issue which helping to reduce the intensity of people reaction on the incidents and educate people on the consequences of these behaviours.